Linking content and language-integrated learning (CLIL) and task-based language teaching (TBLT) in an effective way: a methodological proposal - Lopes, António (2021)
CLIL and TBLT are approaches that have increasingly captured the attention of both teachers and researchers, and many of the latter have already discussed the ways in which they can be brought together. One of the challenges encountered in the implementation of CLIL has been the discrepancy between the level required to carry out the work for content learning and the students' actual level. One of the solutions may lie in resorting to TBLT, where language is regarded as action and the learner seen as a social actor engaged in real-life-like activities. However, in CLIL, the task being proposed to the students has to be appropriate to their level and their ability to internalise conceptual knowledge. In order to bridge some of the methodological gaps between CLIL and TBLT, a framework for designing content-oriented tasks, based on the one advanced for the project PETALL, has been developed to help teachers plan their CLIL activities. After a theoretical introduction to the principles of Task-based Learning and its integration with CLIL, a template designed to systematise the task is provided and discussed.